The Sedimentology and Facies Analysis of the Cretaceous Oceanic Red Beds (CORBs) in the Shiranish Formation, Northern of Iraq - Ahmed , Mohammed Jamal; Tamar-Agha , Mazin Yousif; Alwan , Thamer Abbas (Iraqi Journal of Science, 2021)
Upper Cretaceous Oceanic Red Beds (CORBs) are pelagic sedimentdeposits that deposited in the Upper Cretaceous basin, with widespread inpart of the world as well as in Iraq. This research investigates the depositionof cyclic marl and marly limestone CORBs of six selected sections at theactive southern margin of the Tethys during the Late Campanian -Maastrichtian with petrography, microfacies, and depositional environment.As this study was not a consideration in the past, so decided to visit andidentify all exposure areas of the Upper Cretaceous period rocks are visited.This study involved two fields touring reconnaissance extended fromDarbandikhan city in the east south to Shiranish Village in the west north.Six lithological sections covering the studied area, four sections representCretaceous Oceanic Red Beds (CORBs) and two sections without (CORBs)for the purpose of comparison between them. The sections are described indetail and 250 samples were collected from all studied sections.For the petrography and microfacies analysis 149 thin sections werestudied. The microfacies analysis showing two major successions with RedBed and Non-Red Bed marl and marly limestone, occasionally interbeddedwith thinly beds of shale, sandstone and siltstone. These comprised of fivemicrofacies are Oligostegina Marly Limestone, Globotruncana MarlyLimestone, Marlstone with Microfossils, Red Marlstone, and Red toVariegated Calcareous Sandstone with Radiolarian (Debrise Flow) Making20 thin sections from Gendilly section(GS) (the typical section of this study)for microscopic study of minute fossils (nannofossils) examination, for thisstudy proved that the Cretaceous Oceanic Red Beds (CORBs) dating isMastrichtian age. The Microfossils and nannofossils tests proved thepresence of Danian Age in studied area.This study has proved that the carbonate content in red limestone bedsranged between 53.5-100.0 %, while this percentage ranged in red marlyrocks between 20.5-50.0 %, But in the rocks that do not contain red beds,Carbonate content in limestone rocks ranged between 52.0-100.0 %, and inmarl rocks this ratio ranged between 27.5-49.5 %.